Actividad histórica y análisis de la amenaza del volcán Turrialba, Costa Rica - González Ilama, Gino Steven (2015)
The historic activity of Turrialba volcano was studied based on traveler’s reports and newspapers of the 19th century. In 1864-1866, the volcano was in a period of magmatic eruptions which can be subdivided in two stages: pre-eruptive and eruptive. Ash fall reached distances of ~115 km covering an area of 3400 km2. By means of GIS, we estimated how a similar magmatic eruption as this, could affect the present population and infrastructure, and we conclude that the ash would fall in the most populated areas of Costa Rica, which is important as a prevention measure and an analysis of future risk decision-making. In 2005, Turrialba volcano increased its seismic activity, gas emissions and acid rain, which affected the S, SW and W sectors of the volcano. Afther more than a century without eruption, on 5 January 2010 phreatic activity resumed, with emissions of non-juvenile ash which reached San José. The ash contained cristobalite and hematite, which are unhealthy. Moreover, the eruption formed a nested crater of ~125 m x ~45 m with a NW-SE direction, with emission of SO2 in state of combustion and incandescence, and manifested sporadic ash eruptions. In June 2011, a fumarolic area appeared with temperatures up to ~530 °C in the NW intracrater. On 11 January 2012, a sulfur flow occurred (175 mlong), produced by the heating of the system which also led to phreatic eruptions on 12 and 18 January 2012. Another crater was formed in the eastern extreme of the NW crater.